Procedural unfairness occasioned by unreasonable delay in finalising a disciplinary inquiry: Stokwe v Member of the Executive Council: Department of Education, Eastern Cape [2018] ZACC 3 - Khumalo, Bongani (Obiter, 2020)
“Justice delayed is justice denied” is a legal maxim which denotes that if legal redress is available to a party that has suffered, or is suffering an injustice but is not dispensed timeously, it has the same effect as having no redress at all (see Steenkamp J sentiments in Road Accident Fund v Commission for Conciliation, Mediation and Arbitration [2016] ZALCJHB 139 par 5; see also the definition at Definitions and Translations https://www.definitions.net/definition/justice+delayed+is+justice+denied (accessed 2019-09-12)). In this context, the maxim is used to emphasise that delays in finalising employment disciplinary processes may amount to a denial of justice. Research shows that unreasonable delays in finalising disciplinary cases affect the health and can even cause excruciating distress on the employees concerned (Van der Bank, Engelbrecht and Strumpher “Perceived Fairness of Disciplinary Procedures in the Public Service Sector: An Exploratory Study: Empirical Research” 2008 6(2) SA Journal of Human Resource Management 8).